Education Financing Management in Improving the Quality of Students in Madrasah - Nurhidayatullah; Siti Aimah (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This study aims to analyze how educational financing management can improve the quality of students at Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi. Quality education requires efficient financing management to create a conducive learning environment. This study uses a qualitative approach with a case study design, focusing on financing policies. Data were obtained through interviews with principals, teachers, and education fund managers, as well as related documents. Data analysis used data condensation, data presentation, and drawing conclusions. The results of the study indicate that although the available education funds are quite large, their planning and management are still not optimal, with most of the funds being used for routine expenses. Immature planning results in limited allocation for facility development and improving the quality of teaching. Therefore, policies such as priority-based budgeting, diversification of financing sources, and budget management training need to be implemented to improve the quality of education. With good financing management, learning facilities can be improved, teacher professional development can be prioritized, and student quality can be significantly improved.